THE INFLUENCE OF THE NEW UKRAINIAN SCHOOL IDEA ON THE CONTENT OF THE PRESCHOOL PEDAGOGUES` ACTIVITIES - Hanna Bielienka (Vasyl Stefanyk Precarpathian National University, 2018)
The article analyzes the influence of the concept and main ideas of the New Ukrainian School on the organization of the educational process in preschool educational institutions. The article outlines the main directions of pre-school teachers` activity in need of change: knowing the concept of a new Ukrainian school in order to ensure continuity between preschool institutions and schools, intensification of parent education, implementing flexible schedule for children, rejecting collective classes as the main form of organization of the educational process, providing free choice of activities for children. The author emphasizes the need to revise the content of educational programs for preschool education institutions in order to shift emphasis from cognitive to moral and ethical components of its content. It is noted that the main goal of preschool educational institutions, in accordance with the Basic component of preschool education, is the formation of the vital competence of the child. Key words: preschool educational institution, preschool children, New Ukrainian School, continuity, organization of life sustainability.